חייה ומפעלה הספרותי של לאורה פאפו, "בוכוריטה", המחזאית הראשונה שכתבה בספרדית-יהודית - פאפו אליעזר (מכאן, 2007)
Laura Papo Bohoreta is one of the most active female figures in modern Sephardic history. She was the first female to enter many fields until then reserved for men. She was the first female autodidact field collector of Sephardic folklore, the first female dramatist to arise from within Sephardic community and one of the first Sephardic feminists. This last term, however, should be taken with certain reservation. Bohoreta was definitively a fighter for women’s right to learning and work - but, unlike many feminists, she did not see these objectives as a value per se - but, rather, as a mere commandment of the moment. Understanding Sephardic tradition as an ongoing struggle to keep up with the times, while conserving the old family and community traditions and values, she kept fighting on both fronts, advocating women’s emancipation and striving to preserve the language and the folklore of the community. From an early stage in her life, she discovered that the best instrument through which to pass her message to the community would be theater. From then on, she wrote a variety of folklore and social plays. The article aims at reinstating Bohoreta’s biography around her bibliography.